ANALYSIS OF PROBLEM SOLVING SKILLS BASED ON AUTHENTIC PROBLEMS ASSISTED BY E-MODULE ON SOUND WAVE MATERIAL - Mangasi Holong Rajagukguk; Wawan Bunawan (INPAFI (Inovasi Pembelajaran Fisika), 2023)
Problem solving is one of the 21st century skills that need to be trained through the education process. One of the subjects that can train students' problem solving is physics. Problems in physics learning should be presented as authentic problems in students' daily lives. The purpose of this study is to determine the effect and improvement of students' problem solving due to the effect of the application of e-modules based on authentic problems and conventional learning on the subject matter of sound waves in class XI. This research is a quasi experiment with pre-test and post-test control group design. The results obtained are the percentage of validation assessment results of media experts 88% and material experts 81.25% with valid categories.  Post-test normality test with Kolmogorov-Smirnov test (0.001 < 0.05, 0.006 < 0.05) and Shapiro-Wilk (0.003 < 0.05, 0.022 < 0.05) in experimental and control classes are not normally distributed, Post-test results of experimental and control classes have homogeneous variances (0.478 > 0.050). The results of the final hypothesis test using the Mann-Whitney test obtained that  (6.936> 1.96) and Asymp. Sig. (2-tailed) of 0.000 < 0.05 means that  is rejected and  is accepted. The increase in problem solving skills with the N-gain test of experimental and control class students is 80% and 40% in the high and medium categories.